Analysis of Tunnel Lining Failure Mechanism under the Action of Active Fault - Sujian Ma; Liang Zhang; Dong Wang; XinRong Tan; Sifeng Li; Yang Liu (Shock and Vibration)
The underground structure that crosses the active fault will cause more serious damage under the dislocation of the active fault. Relying on an actual tunnel in the southwest mountainous area to establish a three-dimensional finite element model, the failure mechanism of the tunnel under strike-slip and thrust fault dislocation is revealed from the lining deformation, stress distribution, and plastic zone distribution, and the results show that the damage range of the lining distributes in the area of the fracture and the damage effect is greatly affected by the movement amount of the active fault. The lining damage under the active fault dislocation is mainly tensile damage, while the lining under the thrust fault dislocation shows compression damage on both sides of the fracture when there is a fracture with a large dip angle. The development range of plastic zone is positively correlated with the dip angle of the fracture and the amount of movement, and the development range is negatively correlated with the dip angle of the fracture and positively correlated with the amount of dislocation. The plastic zone range can be predicted, and the key monitoring range can be set according to the movement form of the active fault, the dip angle of the fracture zone, and the amount of fault movement.